Exploring the barriers to athlete personal development within UK Olympic and Paralympic sport - Holden, J.; Wagstaff, C. R. D.; Wadey, R.; Brown, P. (Psychology of Sport and Exercise, 2025)
Elite athletes face a range of challenges throughout their careers including injury, selection, funding status, and retirement. To support athletes to plan for and overcome these challenges, Career Assistance Programs (CAPs) have been developed to support personal and professional development, yet engagement with these services remains low. The aim of this study was to explore the perceived barriers to athletes` engagement with personal development within the UK High-Performance sport system. Underpinned by ontological relativism and epistemological constructivism, 15 elite athletes who were on a funded UK Sport World Class Olympic or Paralympic Program participated in semi-structured interviews. The dataset was analyzed using reflexive thematic analysis. Three themes were developed: The Athlete Bubble, outlines the barrier of the performance-driven culture, Head in the Sand reflects the fear of retirement, and Bridging the Employment Gap highlights the tension of meeting training demands with work opportunities. Findings reveal how cultural expectations, elite sport environments, coach-athlete relationships and scheduling conflicts inhibit athlete engagement with personal development. This study contributes to a deeper understanding of the cultural and systemic barriers that shape how athletes interpret and navigate their development journeys and offers direction for developing more integrated, athlete-centered CAPs.